A study of Tycho's SNR at TeV energies with the HEGRA CT-System - Aharonian, Felix A.; Akhperjanian, A. G.; Barrio, J. A.; Bernlöhr, Konrad; Hermann, G.; Heusler, A.; Hofmann, Werner; Horns, D.; Ibarra, A.; Jung, I.; Kankanyan, R.; Kranich, D.; et al. (Astronomy and astrophysics, 2001)
Tycho's supernova remnant (SNR) was observed during 1997 and 1998 with the HEGRA Čerenkov Telescope System in a search for gamma-ray emission at energies above ~1 TeV. An analysis of these data, ~65 hours in total, resulted in no evidence for TeV gamma-ray emission. The 3σ upper limit to the gamma-ray flux (>1 TeV) from Tycho is estimated at photons cm-2 s-1, or 33 milli-Crab. We interpret our upper limit within the framework of the following scenarios: (1) that the observed hard X-ray tail is due to synchrotron emission. A lower limit on the magnetic field within Tycho may be estimated μG, assuming that the RXTE-detected X-rays were due to synchrotron emission. However, using results from a detailed model of the ASCA emission, a more conservative lower limit μG is derived. (2) The hadronic model of Drury and (3) the more recent time-dependent kinetic theory of Berezhko & Völk. Our upper limit lies within the range of predicted values of both hadronic models, according to uncertainties in physical parameters of Tycho, and shock acceleration details. In the latter case, the model was scaled to suit the parameters of Tycho and re-normalised to account for a simplification of the original model. We find that we cannot rule out Tycho as a potential contributor at an average level to the Galactic cosmic-ray flux.